Effect of antihypertensive medications on thrombolysis therapy and outcomes in acute ischemic stroke patients. Issue 2 (23rd January 2019) - Fleming, Tyler; Blum, Brice; Averkamp, Benjamin; Sullivan, James; Nathaniel, Thomas
Abstract : There are concerns that specific risk factors may alter the benefits of thrombolysis in stroke patients with controlled contraindications including hypertension. The objective of this study was to evaluate the association between clinical risk factors and outcomes in ischemic stroke patients that received thrombolysis therapy pretreated with antihypertensive medications. Using data obtained from a stroke registry, a non‐randomized retrospective data analysis was conducted on patients with the primary diagnosis of acute ischemic stroke with hypertension pretreated with antihypertensive medications. The association between clinical risk factors and functional ambulatory outcome was determined using logistic regression while odd ratios (OR) were used to predict the odds of achieving improved ambulatory outcome in thrombolysis treatment status. Improved or poor functional ambulatory outcome was considered as the end point in our analysis. A total of 4665 acute ischemic stroke patients were identified, of whom 1446 (31.0%) were eligible for thrombolysis, while 3219 were not, and 595 received rtPA, of whom 288 were on antihypertensive medications, while 233 were not. In the rtPA group with antihypertensive (anti‐HTN) medication, only NIHSS score (OR = 1.094, 95% CI, 1.094‐1.000, P  = 0.005) was associated with improved functional outcome while patients with congestive heart failure (OR = 0.385, 95% CI, 0.385‐0.159, P  = 0.035) and patients with a history of previous TIA (OR = 0.302, 95% CI, 0.302‐0.113, P  = 0.017) were more likely to be associated with poor functional outcomes. Congestive heart failure and TIA are independent predictors of functional outcomes in stroke patients pretreated with antihypertensive medications prior to thrombolysis therapy.